PERMASALAHAN PERKOTAAN DAN KECENDERUNGAN PERILAKU INDIVIDUALIS PENDUDUKNYA - Sumardjito, Sumardjito (Cakrawala Pendidikan, 1999)
Lately, urban problems have increasingly becomethe topic of heated discussions due to their relations withalmost all aspects of human living. The development ofurban activities often becomes something that people laytheir hopes on so that they come to the city in great numbersto fight for a chance to earn a living there.it turns out that the rapidity of a city's developmentbrings about a certain social impact as a result of the intenseclimate of competition in the life of its society. The societythen tends to be divided into two segments, namely, (1) thewinning and successful social groups in the competitiveclimate and (2) the losing and defeated social groups.Another deeply felt social impact caused by such a climateis on the social behavior, which tends to become intra- orintersegmentally individualistic. The expression of suchbehavior may take two aspects, i.e., physical and attitudinalaspects, which are always reflected in daily social behavior.From the analysis in this study it can be concludedthat individualistic behavior is the main characteristic ofurban life. Such behavior is impossible to eliminate becauseit emerges from the existing competitive climate. However,it needs to be put under control in order to prevent conflictsbetween individuals or social groups who reside in the city.One means of such control is social education given toinhabitants or potential inhabitants of urban environmentsso that there comes a relationship of mutual need betweenthe individuals and the existing groups.